Cara Menulis Press Release di Media Massa: PkM di Kalurahan Madurejo, Kapanewonan Prambanan Sleman, Daerah Istimewa Yogyakarta - Siti Saudah; Suprih Ambawani; Bernadetta Eko Putranti (JNANADHARMA, 2023)
Abstract The use of Positive language in online learning assistance is very important for the community, especially parents. This Community Service (PkM) activity is intended to provide education to the community, especially parents, in using Positive Language. The object of this activity is PKK women/parents in Kapanewon Moyudan, Sleman, Yogyakarta. The location was chosen because most of the community of PKK mothers/parents work as teachers and as housewives so it is very well targeted. The method used in PkM activities is to provide education through face-to-face counseling with a strict process and given a pretest before counseling and after the activity to find out the benefits of this PkM activity a posttest is carried out. The results of this activity are evident from the posttest results that there is an increase in the understanding of the community/parents in responding to the use of Positive Language, especially in online learning assistance, understanding the psychological impact on children and realizing the importance of parenting/parenting knowledge for parents. This PkM activity is expected to contribute to parenting education to the wider community, so that there is a synergy between the campus and the community. Keywords— Positive Language, Learn online, parents,